Administrative and infrastructural factors affecting library and information science educators’ actual use of educational support systems for teaching in Nigerian universities (2019)
This research assumes that administrative and infrastructural factors may explain the low use of educational support systems (ESS) for teaching by library and information science (LIS) educators in Nigerian universities. The literature has focused on the adoption of different types of educational technologies and their use by teachers and students with little consideration for the LIS educators’ actual use of ESS for teaching and the effect of institutional support on the use of these systems. Thus, the study seeks to determine the user percentage of ESS for teaching, how the educators actually use ESS for teaching, the nature of administrative and infrastructural support they receive while teaching with ESS and whether the two factors correlate with and predict the actual use of ESS for teaching. A descriptive survey design was adopted and data were collected through a questionnaire. The results indicate that many of the LIS educators did not use ESS for teaching and that their actual use of ESS for the instructional activities highlighted in the study was low and below average. Moreover, the educators were found to have received minimal administrative and infrastructural support. The two factors were also found to have significant positive correlations and a significant and positive joint influence on the actual use of ESS for teaching with a joint contribution of 14.7%. Analysis of their relative contributions to the prediction of actual use revealed that, although the two support factors contributed positively, only infrastructural support contributed significantly at 0.05 level of significance. It was therefore recommended that for administrative support to be meaningful, adequate infrastructural facilities should be provided for an appreciable and sustainable use of ESS for teaching.